Implementasi Akad Murabahah dalam Pembiayaan Pensiun Pada Bank Syariah di Indonesia - Ghaly Fathur Rahman; Azril Tirza Saladin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study discusses the implementation of Murabahah contracts in pension financing products at Islamic Banks in Indonesia. This study aims to examine the procedures, mechanisms, characteristics, and obstacles faced in the implementation of Murabahah contracts in pension financing. The research method uses a literature approach and field observation to obtain data and information related to the financing process. The results of the study indicate that the pension financing procedure based on the Murabahah contract has been running in accordance with sharia principles and applicable regulations, starting from submission, document verification, feasibility assessment, to disbursement of funds through the wakalah mechanism. The characteristics of pension financing emphasize the certainty of payment through direct autodebit from pension funds. However, there are several obstacles such as limited customer understanding, regulations that are not yet specific, and the complexity of administrative procedures. This study recommends increasing sharia literacy and strengthening regulations to support the development of sustainable sharia pension financing.